Assessment of mental wellbeing of undergraduate pharmacy students from 14 countries : The role of gender, lifestyle, health-related, and academic-related factors - Elnaem, Mohamed Hassan; Mubarak, Naeem; Mohammed Salim, K. T.; Barakat, Muna M.; Abdelaziz, Doaa H.; Mansour, Noha O.; Thabit, Abrar K.; Ramatillah, Diana Laila; Al-Jumaili, Ali Azeez; Syed, Nabeel Kashan; Adam, Mohammed Fathelrahman; Hossain, Md Sanower; et al. (Frontiers Media S.A., 2022)
Background: Pharmacy students will assume future roles as frontline healthcare providers. Therefore, evaluating their current state of mental wellbeing and its associated factors is essential for better planning students' support initiatives. This study aimed to assess mental wellbeing and its associated factors among undergraduate pharmacy students from 14 countries during the pandemic. Methods: A cross-sectional study was conducted among undergraduate pharmacy students in 14 countries in Asia and the Middle East. The validated Warwick-Edinburgh Mental Wellbeing Scale (the 14-item WEMWBS) was adopted to assess mental wellbeing. Data collection was performed online between February and April 2022. Descriptive and inferential statistics were used as appropriate. Results: A total of 2,665 responses were received, mainly from females (68.7%) with a higher presence of private universities (59.1%). About 34.9% had low mental wellbeing levels, while 57 and 8.1% had medium, and high levels, respectively. Binary logistic regression showed that males (AOR: 1.34; CI 95%: 1.11–1.61; p < 0.01) and students with no chronic illnesses (AOR: 2.01; CI 95%: 1.45–2.80; p < 0.001) were more likely to have higher mental wellbeing. Also, participants who did not engage in any exercise (AOR: 0.71; CI 95%: 0.52–0.98; p = 0.04) and those in public universities (AOR: 0.82; CI 95%: 0.69–0.97; p = 0.02) were less likely to have higher mental wellbeing. Additionally, students who had interest/passion for pharmacy (AOR: 1.69; CI 95%: 1.07–2.68; p = 0.02), and those who known pharmacists inspired (AOR: 1.81; CI 95%: 1.06–3.12; p = 0.03), were more likely to have higher mental wellbeing compared with those who had no specific reason for their choice to study pharmacy. The participants with excellent (AOR: 1.87; CI 95%: 1.29–2.70; p = 0.001) or very good self-reported academic performance (AOR: 1.57; CI 95%: 1.12–2.22; p = 0.01) were more likely to have higher mental wellbeing compared to those with fair academic performance. Conclusion: More than a third of the participants had low mental wellbeing. Various demographic, lifestyle, medical and academic factors appeared to affect students' mental wellbeing. Careful consideration of these factors and their integration into the pharmacy schools' plans for student support services and academic advising would be essential to improve students' mental wellbeing.